The changing law of the employment relationship : comparative analyses in the European context - Countouris, Nicola (Aldershot, 2007)
"During the past few decades, industrialized countries have witnessed a progressive crisis of the regulatory framework sustaining the binary model of the employment relationship based on the subordinate employment/autonomous self-employment dichotomy. New atypical and hybrid working arrangements have emerged, challenging the traditional notions of, and divisions between, autonomy and subordination. This in turn has strained labour law systems across industrialized countries that were previously based on the notion of dependent and subordinate employment to cast their personal scope of application."